Application of Criminal Penalties in Child Protection Law in the State Court Of Ngawi - Sulistyo Utomo; Ira Alia Maerani (Jurnal Daulat Hukum, 2019)
This research aims to identify and analyze the existence of the application of criminal penalties in the handling of criminal cases Child Protection in Indonesia and analyze the effectiveness of criminal fines when viewed from the perspective of children as victims of crime.Method used is socio-juridical using primary and secondary data. Primary data collection technique is done with the interview, and secondary data by reading, reviewing and analyzing primary legal materials, secondary legal materials, tertiary legal materials with qualitative analysis techniques, interpreted logically and systematically and drawn conclusions.Based on the survey results revealed that the existence of the application of criminal penalties in the handling of criminal cases Child Protection in Indonesia criminal fines in criminal prospects are just as an alternative or substitute for imprisonment or confinement. And effectiveness this penalty has not run optimally because the defendant would prefer to replace the criminal penalties to imprisonment.The conclusion of this thesis is that the implementation or execution of criminal penalties in Indonesia have not been effective or not maximized because law enforcement or judges tend to prefer the imprisonment of the criminal finesKeywords: Criminal Fines; Criminal Prison; Children.